Discriminating the non-coordination between ecosystem service value and economic development and its spatial characteristics in central Yunnan urban agglomeration in the recent 30 years - Li, Anlin; Yang, Yehua; Niu, Lede; Luo, Haichao; Chi, Hengxing (Frontiers in Ecology and Evolution, 2024)
Environmental issues have become one of the important topics affecting China and the world. As the world's most populous country and the second-largest economy, China's environmental conditions have significant impacts on global ecosystems and sustainable development. To accurately determine the relationship between economic development and the environment, explore the noncoordination and spatial characteristics between the two, and promote regional sustainable development.This study is based on land-use data from four periods: 1990, 2000, 2010, and 2020. It uses the dynamic measurement and value equivalent method to explore the characteristics of land-use changes and measure the value of ecosystem services in the Central Yunnan Urban Agglomeration. At the same time, the study uses the non-coordination degree model and hotspot analysis tools to identify the non-coordination between Ecosystem Service Value and economic development (Gross Domestic Product) , and explore the spatial characteristics between them. The research results show that: (1) The main land-use types include cultivated land, forest land, and grassland, which account for more than 90% of the total proportion. The land types with a small proportion in the region are water areas, construction land, and unused land. (2) The development level of ecosystem service value presents four types of changes: fluctuating increase, fluctuating decrease, continuous increase, and continuous decrease. The regional spatial distribution shows obvious regional heterogeneity, overall presenting a spatial distribution pattern of "low in the middle, high around." (3) The average index of non-coordination degree from 1990 to 2020 is 0.591, 0.635, 0.584, and 0.565, showing a coordinated non-coordination coupling type. The regional space presents a spatial pattern of "high in the central and western regions, low in the northeastern and southern regions." (4) The hotspots of non-coordination are mainly concentrated in the central and northwest regions of the Central Yunnan Urban Agglomeration, while the coldspots of noncoordination are mainly distributed in the northeastern, western, and southern regions of the Central Yunnan Urban Agglomeration, showing a regular agglomeration distribution. This study suggests that it is necessary to balance and coordinate the relationship between regional economic development and the environment.